67 is the answer to the question
Good morning ☕️
Answer:
-5x(x + 2)
Step-by-step explanation:
<em><u>the key is factoring: </u></em>
-5x² - 10x = -5x × (x) - 5x × (2) {here we notice that -5x is a common factor}
= -5x(x + 2)
_________________________________
:)
We just need the points B and D to solve this. B = (0,6) and D = (3,2).
Add the components together and average them.
midpoint(B,D) = ((0 + 3) / 2) , ((6 + 2) / 2)
= (1.5, 4)
Hopefully this is the right answer.
Are we answering to number 5?
the answer is C -73 gvhfrbguviafgi